Metal soft magnetic powder, surface insulation modification method thereof and soft magnetic composite material

By contacting the boehmite precursor sol with metal soft magnetic powder under low temperature heating conditions, amorphous Al2O3-coated metal soft magnetic powder is obtained, which solves the problem of unsatisfactory bonding of the coating layer to the powder in the prior art, and is suitable for powders such as thermodynamic metastable amorphous, nanocrystalline alloys, etc., achieving stronger binding force and better high-frequency application performance.

CN119517535APending Publication Date: 2025-02-25HUAZHONG UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411690171.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the surface insulation modification method of metal soft magnetic powder has the problem that the coating layer and the powder are not ideally combined, and it is not suitable for metal soft magnetic powders such as thermodynamic metastable amorphous and nanocrystalline alloys.

Method used

By fully contacting the boehmite precursor sol with the metal soft magnetic powder under low temperature heating conditions, amorphous Al2O3-coated metal soft magnetic powder was obtained after dehydration, which solved the problem of unsatisfactory bonding of the coating layer to the powder, and was suitable for powders such as thermodynamic metastable amorphous, nanocrystalline alloys.

Benefits of technology

It realizes a stronger bonding force between the amorphous Al2O3 cladding layer and metal soft magnetic powder, and is suitable for more types of metal soft magnetic powders, reducing the risk of cracking of the cladding layer under pressing conditions, and improving the high-frequency application performance of soft magnetic composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517535A_ABST
    Figure CN119517535A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of soft magnetic materials, and discloses metal soft magnetic powder, a surface insulation modification method of the metal soft magnetic powder and a soft magnetic composite material. The surface insulation modification method of the metal soft magnetic powder comprises the following steps: (1) dispersing boehmite powder in a solvent to prepare boehmite precursor sol; and (2) the boehmite precursor sol and metal soft magnetic powder are mixed, then heating evaporation is conducted till a solvent is completely volatilized, the amorphous Al2O3 coated metal soft magnetic powder is prepared, and the heating temperature ranges from 50 DEG C to 80 DEG C. According to the amorphous Al2O3 coated metal soft magnetic powder prepared through the preparation method, the amorphous Al2O3 coating layer on the surface of the amorphous Al2O3 coated metal soft magnetic powder and the metal soft magnetic powder have higher binding force, and in addition, the amorphous Al2O3 coating layer can meet the low-temperature surface coating modification requirements of the coating layer and thermodynamic metastable state amorphous and nanocrystalline alloy and other metal soft magnetic powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the relevant technical field of soft magnetic material preparation, and more specifically, relates to a metal soft magnetic powder and a surface insulation modification method thereof, and a soft magnetic composite material. Background Art

[0002] Soft magnetic composites (SMC) usually have high saturation magnetization, good DC superposition characteristics and relatively high operating frequency. They are key materials for the design and development of high-frequency and miniaturized magnetic components. The preparation process of soft magnetic composites mainly includes the steps of surface insulation modification of metal soft magnetic powder, mixing with binder for granulation, pressing, curing and annealing. Specifically, the eddy current loss between particles of soft magnetic composites can be effectively reduced by forming an insulating layer on the surface of metal soft magnetic powder through appropriate process. An efficient metal soft magnetic powder surface insulation process is a prerequisite for improving the high-frequency application performance of soft magnetic composites.

[0003] At present, the commonly used methods for surface insulation modification of metal soft magnetic powders include organic coating and inorganic coating. In terms of organic coating, thermosetting polymer materials such as epoxy resin, phenolic resin, and silicone resin are mainly used. Although the modified metal soft magnetic powder has a good insulation effect, the resin coating is easy to decompose and fail during high-temperature treatment; on the other hand, inorganic insulation coating is phosphate formed by surface phosphating reaction, and oxide coatings such as SiO2 or Al2O3. These coatings show high performance in terms of insulation and thermal stability, but these technologies usually have defects such as complex preparation process and difficult to control powder dispersion. Taking Al2O3 coating as an example, conventional preparation methods include sol-gel method and vapor deposition method. Among them, the sol-gel method usually requires high-temperature calcination (600-1200°C) to form an oxide coating layer, and is not suitable for surface modification of metal soft magnetic powders with poor thermal stability or phase structure transformation (such as amorphous alloy soft magnetic powders, Fe-Ni alloys, etc. will undergo structural transformation or phase transformation after high temperature, deteriorating the intrinsic magnetic properties of the powder); and the vapor deposition method has relatively low surface coating efficiency and high processing cost, and it is difficult to meet current industrial production requirements. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a metal soft magnetic powder and a surface insulation modification method thereof, and a soft magnetic composite material. The surface insulation modification method of the metal soft magnetic powder aims to obtain amorphous Al2O3-coated metal soft magnetic powder by fully contacting the boehmite precursor sol with the metal soft magnetic powder under low temperature heating conditions, and dehydrating the metal soft magnetic powder, thereby solving the technical problems of the unsatisfactory combination of the coating layer and the metal soft magnetic powder in the surface insulation modified metal soft magnetic powder in the prior art, and the inability to apply the Al2O3 coating layer to the surface coating modification of metal soft magnetic powders such as thermodynamically metastable amorphous and nanocrystalline alloys.

[0005] To achieve the above object, according to a first aspect of the present invention, a method for surface insulation coating of a metal soft magnetic powder is provided, comprising the following steps:

[0006] (1) dispersing boehmite powder in a solvent to prepare a boehmite precursor sol;

[0007] (2) mixing the boehmite precursor sol with a metal soft magnetic powder, and then heating and evaporating the mixture until the solvent is completely volatilized to obtain an amorphous Al2O3-coated metal soft magnetic powder, so that the surface of the metal soft magnetic powder is insulatingly modified; wherein the heating temperature is 50 to 80°C.

[0008] Preferably, the purity of the boehmite powder is greater than 99%, and the specific surface area is greater than 200 m 2 / g;

[0009] The mass proportion of the boehmite powder in the boehmite precursor sol is 0.1% to 10%.

[0010] Preferably, the mass ratio of the boehmite powder to the metallic soft magnetic powder is 1:(10-1000).

[0011] Preferably, the metal soft magnetic powder is one of carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder;

[0012] The Fe-based amorphous alloy powder includes Fe-Cr-Si-BC, Fe-Si-BC or Fe-Si-BPC; the Ni-based amorphous alloy powder includes Fe-Ni-Si-BC or Fe-Ni-Si-BP; the Co-based amorphous alloy powder includes Fe-Co-Si-BC or Fe-Co-BPC; the Fe-based nanocrystalline powder includes Fe-Si-B-Cu-Nb or Fe-Si-BP-Cu.

[0013] Preferably, the solvent is deionized water, or a mixed solvent of deionized water and an organic solvent; wherein the mass ratio of the organic solvent to the deionized water is 1:9 to 9:1, and the organic solvent is methanol, ethanol or glycerol.

[0014] Preferably, the heating method in the heating evaporation is water bath heating, and the heating time is 1 to 6 hours.

[0015] Preferably, the heating and evaporation until the solvent is completely volatilized includes: first heating the mixture of the boehmite precursor sol and the metal soft magnetic powder in a water bath, and then drying until the solvent is completely volatilized; wherein the drying pressure is 0.01-0.1MPa, the temperature is 50-80°C, and the time is 1-12h.

[0016] According to a second aspect of the present invention, there is provided an amorphous Al2O3-coated soft magnetic metal powder obtained by the surface insulation modification method of the soft magnetic metal powder as described in the first aspect of the present invention.

[0017] According to a third aspect of the present invention, there is provided a metal soft magnetic composite material comprising the metal soft magnetic powder coated with amorphous Al2O3 as described in another aspect of the present invention.

[0018] According to a fourth aspect of the present invention, there is provided a use of the metal soft magnetic composite material as described in the third aspect of the present invention in an inductor or a metal soft magnetic powder core.

[0019] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0020] (1) The surface insulation modification method of the metal soft magnetic powder of the present invention provides a new idea for surface coating modification of metal soft magnetic powder using boehmite. Specifically, the metal soft magnetic powder coated with amorphous Al2O3 is obtained by fully contacting the boehmite precursor sol with the surface of the metal soft magnetic powder under low temperature heating conditions, and dehydrating the metal soft magnetic powder. The amorphous Al2O3 coating layer on the surface has a stronger bonding force with the metal soft magnetic powder. In addition, the amorphous Al2O3 coating layer can meet the low temperature surface coating modification requirements of the coating layer and the metal soft magnetic powder such as thermodynamically metastable amorphous and nanocrystalline alloys.

[0021] (2) Preferably, the boehmite selected in the present invention is dispersed in water to form a hydrosol, which is mixed with the metal soft magnetic powder and dried to form a dry gel on the surface of the metal soft magnetic powder, i.e., a highly insulating Al2O3 coating layer; and the specific surface area of ​​the boehmite powder selected in the present invention is greater than 200 m 2 / g, and has a layered structure with a large number of hydrogen bonds between layers, which helps the boehmite sol to fully spread on the surface of the metal powder, thereby forming a uniform coating layer. On the other hand, the rich hydroxyl groups between the boehmite layers can enhance the bonding force between the sol precursor and the metal powder. Therefore, the bonding force between the dehydrated Al2O3 coating layer and the metal soft magnetic powder is stronger, which can effectively prevent the risk of coating rupture that may occur during the pressing process of the inductor or magnetic powder core.

[0022] (3) Preferably, during the preparation process, the mass ratio of boehmite powder to metal soft magnetic powder is 0.1% to 10%, so as to obtain a thinner amorphous Al2O3 coating layer, which not only helps to reduce losses, but also can maintain a higher effective magnetic permeability. At the same time, by accurately controlling the amount of boehmite added, the thickness of the coating layer can be adjusted. Therefore, this method has the advantages of adjustable coating thickness and simple and fast operation, and can meet the requirements of scale, low cost, safety and environmental protection in industrial production.

[0023] (4) Preferably, the metal soft magnetic powder is selected from one of carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder. Among them, the above-mentioned carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder and Fe-Si-Cr alloy powder are metal soft magnetic powder materials commonly used in the field. However, compared with the prior art, the metal soft magnetic powder involved in the present invention has significant advantages in low-temperature coating, and can adapt to more types of metal soft magnetic powders, especially Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder or Fe-based nanocrystalline powder. Therefore, the present invention can be compatible with more types of metal soft magnetic powders, so that the coating technology has higher versatility in the production process.

[0024] (5) The heating evaporation process of the present invention preferably adopts a water bath heating method, which can provide more uniform heat transfer conditions, thereby helping to form a more uniform coating layer. Compared with the prior art, the heating temperature and time of the present invention are more moderate. In addition, even if a drying method is used after heating, the drying temperature is controlled below 80°C, which is still much lower than the reaction temperature of the traditional liquid or vapor deposition Al2O3 coating layer, so that the obtained coating layer has a higher adjustable range of heat treatment, which is conducive to matching the optimal heat treatment temperature of the metal soft magnetic powder, thereby reducing the overall energy consumption in the production process.

[0025] (6) The product obtained by the present invention is a core-shell structure of Al2O3 coated soft magnetic powder, and the Al2O3 coating layer is amorphous and evenly distributed on the surface of the soft magnetic powder. At the same time, the Al2O3 crystal form is precisely controlled by adjusting the reaction temperature of the heat treatment after molding to adapt to the optimal heat treatment conditions of different metal soft magnetic powders. Specifically, when the reaction temperature is below 500°C (including 500°C), the coating layer is amorphous aluminum oxide; when the reaction temperature is between 500°C and 700°C (including 700°C), the coating layer is mainly composed of γ-alumina; and when the reaction temperature is in the range of 700°C to 1200°C, the coating layer is mainly composed of α-alumina. Compared with the prior art, the aluminum oxide coating layer involved in the present invention has more adjustable crystal types, increases the thermal matching with the soft magnetic composite powder during the heat treatment process after molding, and the layered boehmite sol with a larger specific surface area will produce a more uniform coating layer, thereby jointly reducing the risk of cracking of the coating layer under pressing conditions.

[0026] In addition, the boehmite-coated soft magnetic composite material prepared in this study exhibits better low-loss characteristics than the traditional treatment method (such as the soft magnetic composite material treated with phosphoric acid passivation in Comparative Example 1), which indicates that the coating layer on the surface of the magnetic powder successfully blocks the direct contact between the magnetic powders, thereby reducing eddy current losses in high-frequency applications.

[0027] (7) Furthermore, the application of the soft magnetic composite material prepared by the present invention in inductors or metal soft magnetic powder cores can reduce the high-frequency loss of the soft magnetic composite material due to the excellent coating performance of the amorphous aluminum oxide prepared by boehmite. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope (SEM) image of the Fe-Cr-Si-BC amorphous soft magnetic powder coated with amorphous Al2O3 according to Example 1 of the present invention.

[0029] Figure 2 This is an energy dispersive spectrometer (EDS) analysis diagram of the amorphous Al2O3-coated metal soft magnetic powder prepared in Example 1 of the present invention.

[0030] Figure 3 These are the SEM images and EDS results of the amorphous Al2O3-coated metal soft magnetic powder prepared in Example 4 of the present invention; the left image is the SEM image, and the right image is the EDS test image.

[0031] Figure 4 These are the SEM images and EDS results of the amorphous Al2O3-coated metal soft magnetic powder prepared in Example 5 of the present invention; the left image is the SEM image, and the right image is the EDS test image.

[0032] Figure 5These are the SEM images and EDS results of the amorphous Al2O3-coated metal soft magnetic powder prepared in Example 6 of the present invention; the left image is the SEM image, and the right image is the EDS test image. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0034] According to a surface insulation modification method of a metal soft magnetic powder provided by the present invention, the method comprises the following steps:

[0035] (1) Dispersing boehmite powder in a solvent, and uniformly dispersing the powder by ultrasonic stirring to obtain a boehmite precursor sol.

[0036] Boehmite, also known as diaspore, is a white powdery substance with a chemical formula of AlO(OH) and a layered structure. Moreover, boehmite is dispersed in water to form a hydrosol (Al2O3·H2O). In the present invention and its embodiments, the boehmite used is purchased from Ningbo Jiwei Nano New Material Technology Co., Ltd., and is named high-purity boehmite alumina (including three series: JWN-2N-AH01, JWN-2.5N-AH01 and JWN-3N-AH01), with a purity greater than 99% and a specific surface area greater than 200m 2 In particular, in a specific embodiment, the JWN-2.5N-AH01 series of high-purity boehmite alumina is selected.

[0037] (2) The boehmite precursor sol prepared in step (1) is mixed with an appropriate amount of metal soft magnetic powder, and the mixture is subjected to continuous heating evaporation and mechanical stirring until the liquid component in the mixture is completely volatilized, thereby achieving dehydration, and finally preparing amorphous Al2O3-coated metal soft magnetic powder, thereby completing the insulation modification of the metal soft magnetic powder surface.

[0038] In some embodiments, the solvent is deionized water; or an organic solvent such as methanol, ethanol, propanol, etc. is added to deionized water to adjust its reaction characteristics, and the mass ratio of the organic solvent to deionized water is 1:9 to 9:1.

[0039] In some embodiments, the boehmite powder accounts for 0.1% to 10% of the total mass of the boehmite precursor sol solution.

[0040] In some embodiments, the mass ratio of boehmite powder to metal soft magnetic powder is 1:(10-1000).

[0041] In some embodiments, the metal soft magnetic powder is one of carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder.

[0042] The carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, and Fe-Si-Cr alloy powder involved are all surface insulation modified metal soft magnetic powder materials widely used in this field. The difference is that due to the advantages of low-temperature coating technology, the present invention is compatible with more types of metal soft magnetic powders, and is particularly suitable for Fe-based amorphous alloy powders, Ni-based amorphous alloy powders, Co-based amorphous alloy powders or Fe-based nanocrystalline powders.

[0043] Specifically, the Fe-based amorphous alloy powder includes Fe-Cr-Si-BC, Fe-Si-BC or Fe-Si-BPC; the Ni-based amorphous alloy powder includes Fe-Ni-Si-BC or Fe-Ni-Si-BP; the Co-based amorphous alloy powder includes Fe-Co-Si-BC or Fe-Co-BPC; the Fe-based nanocrystalline powder includes Fe-Si-B-Cu-Nb or Fe-Si-BP-Cu.

[0044] In some embodiments, the heating evaporation method in step (2) is water bath heating; the water bath temperature is 50-80° C., and the time is 1-6 hours.

[0045] In some embodiments, the heating evaporation in step (2) includes first heating the mixture of boehmite precursor sol and metal soft magnetic powder in a water bath, and then drying until the solvent is completely evaporated; wherein the drying pressure is 0.01-0.1 MPa, the temperature is 50-80°C, and the time is 1-12 hours.

[0046] Amorphous Al2O3-coated metal soft magnetic powder is prepared by a surface insulation modification method provided by the invention.

[0047] The Al2O3 coated metal soft magnetic powder is a core-shell structure, and the amorphous Al2O3 coating layer is evenly distributed on the surface of the soft magnetic powder.

[0048] A soft magnetic composite material provided by the present invention comprises Al2O3 coated metal soft magnetic powder obtained by the above surface insulation modification method.

[0049] The preparation method of the soft magnetic composite material is a pressing molding method as exemplified below, but is not limited to other preparation methods of this type of metal soft magnetic composite material, such as cold pressing, hot pressing, hot and cold pressing or injection molding.

[0050] A method for preparing a soft magnetic composite material comprises the following steps:

[0051] (1) mixing the amorphous Al2O3-coated metal soft magnetic powder obtained by the surface insulation modification method of the present invention with a resin binder, granulating and then pressing into a mold;

[0052] (2) subjecting the green metal soft magnetic composite material pressed in step (1) to heat treatment (such as heating and curing or annealing) to obtain a metal soft magnetic composite material.

[0053] In some embodiments, the resin binder includes at least one of epoxy resin, silicone resin, and phenolic resin.

[0054] In some embodiments, the molding pressure in step (1) is 200-2000 MPa, and the heat treatment temperature is 150-800°C.

[0055] In some embodiments, the crystal form of the Al2O3 coating layer (including amorphous aluminum oxide, γ-aluminum oxide and α-aluminum oxide) is controlled by adjusting the temperature of the heat treatment after the composite soft magnetic material is formed.

[0056] In some embodiments, the resin binder accounts for 0.5% to 5% of the mass of the amorphous Al2O3 coated metal soft magnetic powder.

[0057] The metal soft magnetic composite material provided by the present invention is used as an inductor or a metal soft magnetic powder core.

[0058] The following are specific examples and related analysis.

[0059] Example 1

[0060] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0061] (1) Weigh 1 g of boehmite, add it to 200 ml of deionized water, and disperse it by ultrasonic until it is completely dissolved to obtain a boehmite precursor sol.

[0062] (2) Weigh 100 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it in a precursor solution. Ultrasonic stirring is carried out in a water bath at 50°C for 4 h. The coated powder is placed in a vacuum oven and dried at 80°C for 2 h to obtain Fe-Cr-Si-BC amorphous soft magnetic powder coated with amorphous Al2O3.

[0063] (3) The amorphous Al2O3-coated Fe-Cr-Si-BC amorphous soft magnetic powder prepared above was fully stirred with 2g of resin (20ml of acetone solvent) solution, and after the solvent was completely evaporated, the powder was sieved to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0064] (4) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0065] (5) The green body was annealed in air atmosphere at 200°C for 1 hour to obtain a soft magnetic composite material sample.

[0066] Example 2

[0067] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0068] (1) Weigh 2 g of boehmite, add it to 200 ml of deionized water, and disperse it by ultrasonic until it is completely dissolved to obtain a boehmite precursor sol.

[0069] (2) Weigh 100 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it in a precursor solution. Ultrasonic stirring is carried out in a water bath at 50°C for 4 h. The coated powder is placed in a vacuum oven and dried at 80°C for 2 h to obtain Fe-Cr-Si-BC amorphous soft magnetic powder coated with amorphous Al2O3.

[0070] (3) The amorphous Al2O3-coated Fe-Cr-Si-BC amorphous soft magnetic powder prepared above was fully stirred with 2g of resin (20ml of acetone solvent) solution, and after the solvent was completely evaporated, it was sieved to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0071] (4) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0072] (5) The green body was annealed in air atmosphere at 200°C for 1 hour to obtain a soft magnetic composite material sample.

[0073] Example 3

[0074] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0075] (1) Weigh 5 g of boehmite, add it to 200 ml of deionized water, and disperse it by ultrasonic until it is completely dissolved to obtain a boehmite precursor sol.

[0076] (2) Weigh 100 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it in a precursor solution. Ultrasonic stirring is carried out in a water bath at 50°C for 4 h. The coated powder is placed in a vacuum oven and dried at 80°C for 2 h to obtain Fe-Cr-Si-BC amorphous soft magnetic powder coated with amorphous Al2O3.

[0077] (3) The amorphous Al2O3-coated Fe-Cr-Si-BC amorphous soft magnetic powder prepared above was fully stirred with 2g of resin (20ml of acetone solvent) solution, and after the solvent was completely evaporated, it was sieved to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0078] (4) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0079] (5) The green body was annealed in air atmosphere at 200°C for 1 hour to obtain a soft magnetic composite material sample.

[0080] Example 4

[0081] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0082] (1) Weigh 5 g of boehmite and add it to a mixed solution of 15 ml of deionized water and 185 ml of ethanol, and disperse it by ultrasonic until it is completely dissolved to obtain a boehmite precursor sol.

[0083] (2) Weigh 100 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it in a precursor solution. Ultrasonic stirring is carried out in a water bath at 50°C for 4 h. The coated powder is placed in a vacuum oven and dried at 80°C for 2 h to obtain Fe-Cr-Si-BC amorphous soft magnetic powder coated with amorphous Al2O3.

[0084] (3) The amorphous Al2O3-coated Fe-Cr-Si-BC amorphous soft magnetic powder prepared above was fully stirred with 2g of resin (20ml of acetone solvent) solution, and after the solvent was completely evaporated, it was sieved to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0085] (4) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0086] (5) The green body was annealed in air atmosphere at 200°C for 1 hour to obtain a soft magnetic composite material sample.

[0087] Example 5

[0088] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0089] (1) Weigh 5 g of boehmite, add it to a mixed solution of 5 ml of deionized water and 195 ml of ethanol, and disperse it by ultrasonic until it is completely dissolved to obtain a boehmite precursor sol.

[0090] (2) Weigh 100 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it in a precursor solution. Ultrasonic stirring is carried out in a water bath at 50°C for 4 h. The coated powder is placed in a vacuum oven and dried at 80°C for 2 h to obtain Fe-Cr-Si-BC amorphous soft magnetic powder coated with amorphous Al2O3.

[0091] (3) The amorphous Al2O3-coated Fe-Cr-Si-BC amorphous soft magnetic powder prepared above was fully stirred with 2g of resin (20ml of acetone solvent) solution, and after the solvent was completely evaporated, it was sieved to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0092] (4) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0093] (5) The green body was annealed in air atmosphere at 200°C for 1 hour to obtain a soft magnetic composite material sample.

[0094] Example 6

[0095] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0096] (1) Weigh 10 g of boehmite, add it to 100 ml of deionized water, and disperse it by ultrasonic until it is completely dissolved to obtain a boehmite precursor sol.

[0097] (2) Weigh 100 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it in a precursor solution. Ultrasonic stirring is carried out in a water bath at 50°C for 4 h. The coated powder is placed in a vacuum oven and dried at 80°C for 2 h to obtain Fe-Cr-Si-BC amorphous soft magnetic powder coated with amorphous Al2O3.

[0098] (3) The amorphous Al2O3-coated Fe-Cr-Si-BC amorphous soft magnetic powder prepared above was fully stirred with 2g of resin (20ml of acetone solvent) solution, and after the solvent was completely evaporated, it was sieved to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0099] (4) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0100] (5) The green body was annealed in air atmosphere at 200°C for 1 hour to obtain a soft magnetic composite material sample.

[0101] Example 7

[0102] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0103] (1) Weigh 3 g of boehmite, add it to a mixed solution of 15 ml of deionized water and 185 ml of ethanol, and disperse it by ultrasonic until it is completely dissolved to obtain a boehmite precursor sol.

[0104] (2) Weigh 100 g of Fe-Si soft magnetic powder and place it in a precursor solution. Ultrasonic stirring is performed in a water bath at 50° C. for 4 h. The coated powder is placed in a vacuum oven and dried at 80° C. for 2 h to obtain amorphous Al2O3-coated Fe-Si soft magnetic powder.

[0105] (3) The amorphous Al2O3-coated Fe-Si soft magnetic powder prepared above was fully stirred with 1g of resin (20ml of acetone solvent) solution, and after the solvent was completely evaporated, the powder was sieved to obtain Fe-Si alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0106] (4) The granulated powder is pressed at 2000 MPa to obtain a soft magnetic composite material green body.

[0107] (5) The green body was annealed in an argon atmosphere at 750°C for 1 hour to obtain a soft magnetic composite material sample.

[0108] Example 8

[0109] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0110] (1) Weigh 3 g of boehmite, add it to a mixed solution of 15 ml of deionized water and 185 ml of ethanol, and disperse it by ultrasonic until it is completely dissolved to obtain a boehmite precursor sol.

[0111] (2) Weigh 100 g of Fe-Si soft magnetic powder and place it in a precursor solution. Ultrasonic stirring is carried out in a water bath at 70°C for 4 h. The coated powder is placed in a vacuum oven and dried at 80°C for 2 h to obtain amorphous Al2O3-coated Fe-Si soft magnetic powder.

[0112] (3) The amorphous Al2O3-coated Fe-Si soft magnetic powder prepared above was fully stirred with 1g of resin (20ml of acetone solvent) solution, and after the solvent was completely evaporated, the powder was sieved to obtain Fe-Si alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0113] (4) The granulated powder is pressed at 2000 MPa to obtain a soft magnetic composite material green body.

[0114] (5) The green body was annealed in an argon atmosphere at 750°C for 1 hour to obtain a soft magnetic composite material sample.

[0115] Comparative Example 1

[0116] This embodiment provides a method for preparing the above-mentioned metal soft magnetic composite material, which comprises the following steps:

[0117] (1) Weigh 0.6 g of phosphoric acid in 20 ml of ethanol and disperse by ultrasonic until it is completely dissolved to obtain a phosphoric acid passivation solution.

[0118] (2) Weigh 100 g of Fe-Cr-Si-BC amorphous soft magnetic powder and place it in a phosphoric acid passivation solution. Stir it in a water bath at 65° C. until it is completely dry to obtain a surface-coated modified Fe-Cr-Si-BC amorphous soft magnetic powder.

[0119] (3) The coated modified Fe-Cr-Si-BC amorphous soft magnetic powder prepared above was fully stirred with 2g of resin (20ml of acetone solvent) solution, and after the solvent was completely evaporated, it was sieved to obtain Fe-Cr-Si-BC alloy powder granules with a particle size range of 40 mesh to 200 mesh.

[0120] (4) The granulated powder is pressed at 600 MPa to obtain a soft magnetic composite material green body.

[0121] (5) The green body was annealed in air atmosphere at 200°C for 1 hour to obtain a soft magnetic composite material sample.

[0122] like Figure 1 , which is a SEM image of the Fe-Cr-Si-BC amorphous soft magnetic powder prepared in Example 1 of the present invention, shows that there is a uniform coating layer on the surface of the powder.

[0123] like Figure 2-5 As shown, the microscopic morphology and surface element distribution test of the amorphous Al2O3-coated soft magnetic metal powder in Examples 1, 4, 5 and 6 respectively correspond. The SEM images corresponding to Examples 1, 4, 5 and 6 show that there is a uniform coating on the surface of the soft magnetic metal powder, and the surface element distribution test diagram shows that there is a coating layer rich in Al elements on the powder surface.

[0124] The effective permeability and DC bias performance of the samples of Examples 1, 4, 6 and Comparative Example 1 are shown in Table 1;

[0125] Table 1: Effective permeability and DC bias performance of samples prepared by different processes

[0126] performance Example 1 Example 4 Example 6 Comparative Example 1 Effective magnetic permeability 18.5 17.6 12.1 15.6 DC bias performance (%) 84.7 84.9 89.3 90.1

[0127] The power loss (P cv ), as shown in Table 2:

[0128] Table 2: Power loss (P cv :mW / cm 3 )

[0129]

[0130] Table 2 shows the power loss (P cv ), it can be seen that the soft magnetic composite material sample prepared by the present invention has relatively low loss characteristics. The method is also applicable to Fe-Si powder, and its magnetic properties are shown in Table 3.

[0131] Table 3: Soft magnetic properties of FeSi samples

[0132]

[0133] about Figures 3 to 5 The text marks in the EMS image on the left correspond to the test points of EDS. In the drawings of the present invention, the text marks are not processed to avoid damaging the morphology in the initial morphology image.

[0134] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.

Claims

1. A method for surface insulation modification of metal soft magnetic powder, characterized in that: The following steps are involved: (1) dispersing boehmite powder in a solvent to prepare a boehmite precursor sol; (2) mixing the boehmite precursor sol with a metal soft magnetic powder, and then heating and evaporating the mixture until the solvent is completely volatilized to obtain an amorphous Al2O3-coated metal soft magnetic powder, so that the surface of the metal soft magnetic powder is insulatingly modified; wherein the heating temperature is 50 to 80°C.

2. The surface insulation modification method of the metal soft magnetic powder according to claim 1, characterized in that: The boehmite powder has a purity greater than 99% and a specific surface area greater than 200 m 2 / g; The mass proportion of the boehmite powder in the boehmite precursor sol is 0.1% to 10%.

3. The surface insulation modification method of the metal soft magnetic powder according to claim 1, characterized in that: The mass ratio of the boehmite powder to the metal soft magnetic powder is 1:(10-1000).

4. The surface insulation modification method of the metal soft magnetic powder according to claim 1, characterized in that: The metal soft magnetic powder is one of carbonyl iron powder, Fe-Ni-Mo alloy powder, Fe-Ni alloy powder, Fe-Co alloy powder, Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Si-Cr alloy powder, Fe-based amorphous alloy powder, Ni-based amorphous alloy powder, Co-based amorphous alloy powder and Fe-based nanocrystalline powder; The Fe-based amorphous alloy powder includes Fe-Cr-Si-BC, Fe-Si-BC or Fe-Si-BPC; the Ni-based amorphous alloy powder includes Fe-Ni-Si-BC or Fe-Ni-Si-BP; the Co-based amorphous alloy powder includes Fe-Co-Si-BC or Fe-Co-BPC; the Fe-based nanocrystalline powder includes Fe-Si-B-Cu-Nb or Fe-Si-BP-Cu.

5. The surface insulation modification method of the metal soft magnetic powder according to claim 1, characterized in that: The solvent is deionized water, or a mixed solvent of deionized water and an organic solvent; wherein the mass ratio of the organic solvent to the deionized water is 1:9 to 9:1, and the organic solvent is methanol, ethanol or glycerol.

6. The surface insulation modification method of the metal soft magnetic powder according to claim 1, characterized in that: The heating is water bath heating, and the heating time is 1 to 6 hours.

7. The surface insulation modification method of the metal soft magnetic powder according to claim 1, characterized in that: The heating evaporation comprises first heating the mixture of the boehmite precursor sol and the metal soft magnetic powder in a water bath and then drying it; wherein the drying pressure is 0.01-0.1 MPa, the temperature is 50-80° C., and the time is 1-12 hours.

8. Amorphous Al2O3-coated metal soft magnetic powder obtained by the surface insulation modification method according to any one of claims 1 to 7.

9. A metal soft magnetic composite material, characterized in that: Contains the amorphous Al2O3-coated metal soft magnetic powder as claimed in claim 8.

10. Use of the metal soft magnetic composite material according to claim 9 in an inductor or a metal soft magnetic powder core.

Citation Information

Patent Citations

  • Method for preparing 3D printing cobalt-based ceramic composite powder for dental department

    CN107309423A

  • Method for ball-milling modified sol-gel coated magnetic powder core

    CN112185642A

  • Soft magnetic composite powder and preparation method thereof

    CN115394512A

  • Magnetic powder for magnetic recording medium

    US20160217817A1

  • Soft magnetic composite materials and methods and powders for producing the same

    US20210142933A1